Challenges and Opportunities to Achieve Digital Maturity in Healthcare: A Literature Review - Putra, Dewa Ngakan Gde Wahyu Mahatma; Khoiri, Abu; Naya, Aulia Riswanti (Universitas Muhammadiyah Yogyakarta, 2024)
Digital transformation in the healthcare sector offers many benefits, but achieving it requires good digital maturity. This study aimed to identify the role of digital maturity in innovative healthcare, challenges, opportunities, and recommendations that could be applied in an effort to achieve digital maturity. This study used a systematic literature review method by extracting articles from the Scopus, PubMed, and Google Scholar databases in the last 10 years using the keywords